Current methods in the diagnosis of invasive meningococcal disease - Ciftci, Ergin; Ocal, Duygu; Somer, Ayper; Tezer, Hasan; Yilmaz, Dilek; Bozkurt, Sirac; Dursun, Oldac Uras; Merter, Şeyhmus; Dinleyici, Ener Cagri (Frontiers in Pediatrics, 2025)
Invasive meningococcal disease (IMD) remains a significant health concern due to its global distribution, potential for epidemic spread, unpredictable nature, rapid progression, and high mortality rates or permanent sequelae. The global elimination of meningococcal illness via immunization is a primary objective of the World Health Organization's strategy to defeat meningitis by 2030. Timely recognition of meningococcal infection and immediate, precise, and specific identification of Neisseria meningitidis are essential for optimal clinical management and enhanced outcomes, monitoring evolving meningococcal epidemiology, detecting outbreak activity, and providing an effective public health response. Clinical findings, microscopic findings, Gram stains, and cultures are traditional and widely used diagnostic methods for the definition of IMD, despite some disadvantages. Real-time polymerase chain reaction (rt-PCR) and whole genome sequencing (WGS) are more accurate techniques for the identification of N. meningitidis and subsequent investigation; however, their cost and limited availability present issues. WGS has numerous uses, including strain characterization, population genomics, antibiotic resistance monitoring, and outbreak investigation. New-generation molecular technologies have been and will be used for designing meningococcal vaccines, as well as to monitor dynamic molecular meningococcal seroepidemiology. Microbiology reference laboratories are important, and the digital records and expertise they provide benefit public health for N. meningitidis, as well as other pathogens. While there has been significant progress in the development of meningococcal infection diagnostic tools, it is probable that a combination of approaches or new strategies will still be necessary. The goal of this review was to evaluate the current methods for diagnosing IMD and to discuss diagnostic challenges in practice.